AUTOMORPHISM GROUPS IN LOTUS GRAPH AND UNIFORM BOW GRAPH - Khotimah, Husnul; Dewi, Novi Rustiana (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2025)
This research aims to explore the connection between abstract algebraand graph theory through the study of lotus graph and uniform bow graph. The focus ison determining all automorphisms of both graphs and analyzing the algebraic structurethey form. It is shown that the set of automorphisms, under composition, satisfies thegroup axioms, thus illustrating a natural link between group theory and graph theory.Keywords: Automorphism group, lotus graph, uniform bow graph.